Comparison of the effectiveness and safety between gabapentin and amitriptyline in pain improvement in peripheral diabetic neuropathy patients: a review - Rachmania, Nindita; Probosuseno; Fita Rahmawati (Indonesian Journal of Pharmacology and Therapy, 2024)
Neuropathy pain is one chronic pain that is difficult to treat and has not had an ideal curative therapy, yet. Gabapentin and amitriptyline are widely used as diabetic neuropathy therapies. However, their effectiveness is still debatable and their side effect has been reported. Several factors affect the efficacy and morbidity of gabapentin and amitriptyline in diabetic neuropathy patients. Some treatment options for diabetic neuropathy are available in clinical setting, therefore evaluation the effectiveness of the treatment options is needed to choose the best treatment. This review article evaluated the effectiveness and safety between gabapentin and amitriptyline as pain relief in peripheral diabetic neuropathy (PDN) patients. It was a narrative review using electronic databases such as Science Direct, Scopus and PubMed. The results showed that effectiveness and safety of gabapentin is better than amitriptyline in relief pain on PDN.